Exercise and the Microbiome: Mechanistic Perspectives of the Impact of Exercise on the Gut-Vascular Axis - Marc D. Cook (American Society for Microbiology, 2021)
Given the participation of the microbiome in human health and disease, understanding the context of host-microbe interactions involved in vascular pathophysiology is now evolving through identifying microbial communities, specific taxa, and metabolic profiling which can be coupled to human health outcomes. Exercise has been used to define mechanisms related to improved vascular health, which may involve the microbiome.